Crystallographic binding studies of rat peroxisomal multifunctional enzyme type 1 with 3‐ketodecanoyl‐CoA: capturing active and inactive states of its hydratase and dehydrogenase catalytic sites. Issue 12 (2nd December 2020) - Sridhar, Shruthi; Schmitz, Werner; Hiltunen, J. Kalervo; Venkatesan, Rajaram; Bergmann, Ulrich; Kiema, Tiila-Riikka; Wierenga, Rikkert K.
Abstract : The 1.7 Å resolution crystal structure of peroxisomal multifunctional enzyme type 1 (MFE1) shows a conformation in which both catalytic sites are noncompetent. An analysis of the structures of its complexes with 3‐ketodecanoyl‐CoA suggests how conformational flexibility of MFE1 could be important for its function. Abstract : The peroxisomal multifunctional enzyme type 1 (MFE1) catalyzes two successive reactions in the β‐oxidation cycle: the 2 E ‐enoyl‐CoA hydratase (ECH) and NAD + ‐dependent 3 S ‐hydroxyacyl‐CoA dehydrogenase (HAD) reactions. MFE1 is a monomeric enzyme that has five domains. The N‐terminal part (domains A and B) adopts the crotonase fold and the C‐terminal part (domains C, D and E) adopts the HAD fold. A new crystal form of MFE1 has captured a conformation in which both active sites are noncompetent. This structure, at 1.7 Å resolution, shows the importance of the interactions between Phe272 in domain B (the linker helix; helix H10 of the crotonase fold) and the beginning of loop 2 (of the crotonase fold) in stabilizing the competent ECH active‐site geometry. In addition, protein crystallographic binding studies using optimized crystal‐treatment protocols have captured a structure with both the 3‐ketodecanoyl‐CoA product and NAD + bound in the HAD active site, showing the interactions between 3‐ketodecanoyl‐CoA and residues of the C, D and E domains. Structural comparisons show the importance of domain movements, in particular of the C domain with respect to the D/E domains and of the A domain with respect to the HAD part. These comparisons suggest that the N‐terminal part of the linker helix, which interacts tightly with domains A and E, functions as a hinge region for movement of the A domain with respect to the HAD part.